A yolk-shell eGaSn@Void@SiO2 nanodroplet design for high-performance cathodes in room temperature liquid metal batteries. (1st February 2023) - Wang, Kaizhao; Hu, Jin; Chen, Tianyou; Wang, Kaijun; Deng, Zhongshan; Wu, Jun; Feng, Yongjin; Chen, Qingming; Zhang, Weijun
Abstract: Gallium-based liquid alloys that exhibit high capacity and self-healing properties have been demonstrated to be promising cathodes for room temperature liquid metal batteries (RTLMBs). However, the electrochemical performances of these alloys are poor due to severe volume expansion and an unstable solid electrolyte interface layer during the lithiation process. Here, a sol-gel strategy was performed to construct yolk-shell structure nanodroplets (eGaSn@Void@SiO2 ) that contain sufficient void space by amorphous silicon oxide, which generated a liquid metal electrode with a high performance. The amorphous SiO2 shells not only play an important role in building stable SEI films, providing efficient electron/ion conduction channels and preventing agglomeration of active substances, but exhibit good elastic behavior during charging/discharging. Due to the appropriate voids in the yolk-shell structure, the eGaSn nanodroplets can expand freely without breaking or disrupting the electrode structure; thus, the resulting eGaSn@Void@SiO2 NDs exhibited high capacities of 538, 454, and 338 mA h g −1 at current rates of 0.2, 1 and 5 C, respectively. No obvious decay was observed with more than 500 cycles and a capacity of 377 mA h g −1 at 2 C. Interestingly, the density functional theory (DFT) calculations revealed that the effective chemisorption between the discharge products and SiO2 provides sufficient electrical contact sites with a significant drop in electrochemical impedance during cycling. The causes of the superior electrodes performance were investigated in depth using in situ X-ray diffraction and theoretical calculations. Our rational design may shed unprecedented light on the development of liquid alloy-based cathodes for high-performance RTLMBs.